Students’ Access to and Perception of Using Mobile Technologies in the Classroom: the Potential and Challenges of Implementing Mobile Learning - Muhammad Hanif; Asrowi Asrowi; Sunardi Sunardi (Journal of Education and Learning (EduLearn), 2018)
In implementing mobile learning system, students’ needs and perceptions should be focused upon along with curriculum standards. Particularly in the context of higher education institutions in Indonesia, some schools authorities have refused to implement m-learning. Although m-learning is widely used in some schools and considered an effective educational tool, it is not yet fully utilised in most Indonesian schools. Therefore, the aim of this study is to investigate students’ access to and perception of the use of mobile devices in learning, and to understand the potential for its implementation. This study is the result of a survey conducted on 61 students in a school which banned the use of mobile technology. It seeks to understand their potential accessibility by means of ownership, interaction time and the types of mobile application used and to find their perceptions through agreement and the reasons for adopting mobile learning in the classroom. The findings indicate that students are very familiar with mobile devices and their applications. The results also reveal that students have positive perceptions toward m-learning, and indicate that mobile technologies are widely used among them. This report can be taken as the basis for applying a mobile learning system in the classroom.